Arthur White Collection, Correspondence from London division via Arthur White to Time Medicine and Press, article draft, 2. - White, Arthur (Time Magazine; Digitized from original print, Valdosta State University Archives and Special Collections, December 8, 2016., 1978)
Correspondence from London division via Arthur White to Time Medicine and Press with article draft in reference to the birth of the first "test-tube baby" by Lesley and John Brown in Oldham, England in 1978 by doctors Patrick Steptoe (Gynecologist) and Robert Edwards (Physiologist).
Digitized from original print, Valdosta State University Archives and Special Collections, December 8, 2016.
Keywords: Test tube baby; In Vitro Fertilization; IVF; Steptoe-Edwards Fertilization Technique; Time Magazine; Time Magazine Medicine; Time Medicine; Arthur White; Lesley Brown; John Brown; Lousie Joy Brown; Patrick Steptoe; Oldham General Hospital; Oldham, England; London, England; England; Great Britain; 1970s; 1978